An inhibitory RNA aptamer against the lambda cI repressor shows transcriptional activator activity in vivo. Issue 10 (2nd May 2017) - Ohuchi, Shoji; Suess, Beatrix
Abstract : RNA aptamers are one of the promising components for constructing artificial genetic circuits. In this study, we developed a transcriptional activator based on an RNA aptamer against one of the most frequently applied repressor proteins, lambda phage cI. In vitro selection (Systematic Evolution of Ligands by EXponential enrichment) and following in vivo screening identified an RNA aptamer with the intended transcriptional activator activity from an RNA pool containing a 40‐nucleotide long random region. Quantitative analysis showed a 35‐fold elevation of reporter expression upon aptamer expression. These results suggest that the diversity of artificial transcriptional activators can be extended by employing RNA aptamers against repressor proteins to broaden the parts for constructing genetic circuits. Abstract :